Evaluation of a composite soil health index and soil microbiome in a regenerative agriculture cocoa chronosequence - Jennifer Schmidt; Thomas Fungenzi; Alexander Recamán; Sat Darshan S. Khalsa (Ecological Indicators, 2025)
Cultivation of cocoa (Theobroma cacao L.) can lead to soil degradation in the absence of good agricultural management. Integrating regenerative agriculture practices such as cover crops and agroforestry could help mitigate potential negative effects of continuous cocoa cultivation on the soil, but the impacts of these practices on soil health and the soil microbiome have not been assessed empirically. Composite soil health indices calculated from multiple indicators represent a promising method to measure complex changes in soil functioning and can be complemented by amplicon sequencing. A soil health assessment with eighteen indicators of three functions (carbon transformations, nutrient cycling, and structure maintenance) was conducted across a chronosequence consisting of plots at the same farm under different durations of cocoa cultivation with regenerative practices. Correlations were calculated between soil health index scores and soil microbiome metrics (e.g. community structure, diversity, and relative abundance). Soil health was maintained over time despite changes in specific indicators. Biological activity, earthworm counts, pH, P, and K increased with increasing duration of cocoa cultivation, while scores for surface aggregation, soil structure, and residual nitrate declined. A critical evaluation of this method of evaluating soil health is presented. The results of this study underscore the potential for cocoa grown with regenerative practices to maintain or improve rather than degrade soil and can be used to formulate specific recommendations to promote soil health.